EFFECTIVENESS OF LEVEL 1 PROGRESSIVE MOBILIZATION ON DECREASED INTRACRANIAL ADAPTIVE CAPACITY IN HEMORRHAGIC STROKE CASES - Ilhamsyah (Universitas Islam Negeri Alauddin Makassar, 2023)
The prevalence of stroke diagnosed by doctors in Indonesia in 2018 was aged ≥ 15 years (10.9%) or an estimated 2,120,362 people. South Sulawesi has the highest prevalence of stroke based on diagnosis and symptoms reported by health workers. Hemorrhagic stroke is a stroke caused by rupture of a blood vessel in the brain, which results in downstream ischemia and hypoxia. One of the interventions that can be done to overcome the decrease in intracranial adaptive capacity is to perform stage progressive mobilization. The purpose of the case study was to carry out nursing care in hemorrhagic stroke patients with reduced intracranial adaptive capacity using level 1 progressive mobilization interventions in the ICU RSUP. Dr. Wahidin Sudirohusodo Makassar. The method used is a case study with data collection techniques through observation, interviews, physical examination and documentation. The results showed that level 1 progressive mobilization once a day for 3 days before and after the intervention found that level 1 progressive mobilization could be used to stabilize blood pressure, level of consciousness and oxygen saturation. The conclusion based on the results show that the implementation of level 1 progressive mobilization showed that on the first day to the third day of implementation there was an increasing in hemodynamic state, in this case the blood pressure improved, oxygen saturation increased and the level of consciousness increased. This indicates that level 1 progressive mobilization is effective in patients who have problems with decreased intracranial adaptive capacity